CRITICAL AND CREATIVE THINKING FOR YOUNG LEARNERS: ASKING QUESTIONS AND GIVING ANSWERS IN ONLINE LEARNING CONTEXT - Atalya Agustin (UICELL, 2021)
Critical and creative thinking are significant competences for 21st century skills. Young learners should be prepared to develop these skills at school to prepare them for life. Classroom, on-site or virtually, should be a situated environment to support critical and creative thinking development. Teacher and students should approach every problem or case using both competences (Birgili, 2015). To be able to create such an environment, teacher should be insightful on how to intentionally ignite both competences and develop them aligned with students' levels. One of the ways to do this is by asking questions to students. The questions being delivered in the classroom are not simple questions. They are deep and insightful questions. To be able to create such questions, teacher needs to possess questioning skill which could trigger critical and creative thinking in young learners. Moreover, teacher needs to be more concerned on how these skills are being developed in the context of online learning for young learners. This research aims to expose the descriptive accounts of teaching and learning process in online learning setting which is related to critical and creative thinking. This research will be a case study which uses observation and interview as data collection techniques. Keywords: Critical-Creative Thinking, Questioning. Young Learners